2007
DOI: 10.1128/mcb.02155-06
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of CREB-Binding Protein in the Circadian Clock System of Drosophila melanogaster

Abstract: Rhythmic histone acetylation underlies the oscillating expression of clock genes in the mammalian circadian clock system. Cellular factors that contain histone acetyltransferase and histone deacetylase activity have been implicated in these processes by direct interactions with clock genes, but their functional relevance remains to be assessed by use of appropriate animal models. Here, using transgenic fly models, we show that CREBbinding protein (CBP) participates in the transcriptional regulation of the Dros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
49
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 61 publications
6
49
0
5
Order By: Relevance
“…Consistent with our results, a parallel study by Lim et al (34) found a role for nej in the Drosophila circadian clock. From the finding of low expression levels of CLK⅐CYC-dependent genes after constitutive overexpression of nej it was concluded that NEJ acted as a repressor on CLK⅐CYC function.…”
Section: Q7supporting
confidence: 82%
“…Consistent with our results, a parallel study by Lim et al (34) found a role for nej in the Drosophila circadian clock. From the finding of low expression levels of CLK⅐CYC-dependent genes after constitutive overexpression of nej it was concluded that NEJ acted as a repressor on CLK⅐CYC function.…”
Section: Q7supporting
confidence: 82%
“…One HAT shown to interact with CLK is the CBP ortholog NEJIRE (22,29). In one case NEJIRE/CBP was found to act as a transcriptional coactivator (22), but other evidence shows that overexpression of NEJIRE has a negative effect on CLK-CYC-mediated transcription (29). It is possible that the reduced levels of CLK-CYC-dependent gene expression observed after nejire overexpression are due to circadian feedback compensation and that nejire/CBP is indeed a coactivator (22).…”
mentioning
confidence: 99%
“…Another possibility is that CLK interacts with other HATs. One HAT shown to interact with CLK is the CBP ortholog NEJIRE (22,29). In one case NEJIRE/CBP was found to act as a transcriptional coactivator (22), but other evidence shows that overexpression of NEJIRE has a negative effect on CLK-CYC-mediated transcription (29).…”
mentioning
confidence: 99%
“…Ectopic expression of Clock induces the expression of tim, and sometimes per in individual S2 cell lines (see Fig. 1) (McDonald and Rosbash 2001;Lim et al 2007). …”
Section: S2 Cells and Nuclear Translocation Of Per And Timmentioning
confidence: 99%